Application of deep learning algorithms for automated detection of arrhythmias with ECG beats - Oh, Shu Lih (2019)
Arrhythmia is the anomalies of cardiac conduction system that is characterized by abnormal heart rythms. Prolong arrhythmias are life threatening and can often lead to other cardiac diseases. Abnormalities in the conduction system is reflected upon the morphology of the electrocardiographic (ECG) signal and the assessment of these signal can be extremely challenging and time-consuming. Morphological features of arrythmias ECG signals are low in amplitudes and the changes within can sometimes be very subtle. Therefore, the main aim of this study is to develop an automated computer aided diagnostic (CAD) system that can potentially expedite the process of arrhythmia diagnosis, which will allow the clinicians to provide better care and timely intervention for the patient.